The effect of subacromial decompression on the curative effect of arthroscopic treatment of shoulder calcific tendinitis - Zhao, Feng; Wu, Jianbo; Wang, Dong; Li, Peng; Tian, Wei; Li, Wenzheng; Chai, Bo; Zhang, Yuming (Frontiers in Surgery, 2023)
Objective To observe and analyze the surgical efficacy of arthroscopic debridement of calcified deposits and arthroscopic debridement combined with subacromial decompression in patients with supraspinatus tendon calcific myositis. To observe the effect of Subacromial decompression on the efficacy of arthroscopic treatment of shoulder calcific tendinitis. Patients and methods From 2016 to 2021, 48 cases of shoulder arthroscopic debridement due to supraspinatus calcific tendinitis met the inclusion criteria and were included, with 24 cases assigned to the arthroscopic debridement group and 24 cases to the arthroscopic debridement combined with subacromial decompression group. Changes between preoperative and postoperative shoulder pain and shoulder function were statistically analyzed. Results The 24 patients in the arthroscopic debridement group were better than the arthroscopic debridement combined with subacromial decompression group in terms of short-term postoperative shoulder pain and shoulder joint function recovery (p＜0.05). There was no significant difference in the postoperative long-term shoulder pain and shoulder function recovery between the two groups (p > 0.05). Conclusions Compared with arthroscopic debridement combined with subacromial decompression, arthroscopic debridement alone is a better surgical option for the treatment of calcific tendinitis.